Education in coordinates of Industry 4.0 and Industry 5.0 - Bazić, Jovan R; Sekulić, Bojana (Sociološki pregled, 2023)
Industry 4.0 (I4.0) and Industry 5.0 (I5.0) are based on knowledge acquired in education and organized in the form of scientific research activities and materialized in technological innovations, new products and services. The aim of this paper is to consider various aspects of the mutual relationship between education and technologies I4.0 and I5.0. In addition to the fact that education affects the development of technological innovations, the production of new knowledge and educational profiles; technologies I4.0 and I5.0 have a direct impact on education, from changes in the organizational structure of educational institutions and teaching programmes, through the introduction of new technologies and knowledge in teaching, changes in learning methods, to the establishment of the obligation of continuous professional development of teachers. Since this paper has a theoretical character, the content analysis and the synthetic method will be mainly applied in it in order to arrive at relevant results.